Oxford Research Encyclopedia of Natural Hazard Science 2017
DOI: 10.1093/acrefore/9780199389407.013.281
|View full text |Cite
|
Sign up to set email alerts
|

Societal Impacts of Flood Hazards

Abstract: Floods remain the most devastating natural hazard globally, despite substantial investments in flood prevention and management in recent decades. Fluvial floods, such as the ones in Pakistan in 2010 and Thailand in 2011, can affect entire countries and cause severe economic and human losses. Also, coastal floods can inflict substantial harm owing to their destructive forces in terms of wave and tidal energy. A flood type that received growing attention in recent years is flooding from pluvial events (heavy rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Furthermore, a core epistemological limitation with very practical implications results from the research being overwhelmingly focused on understanding the effectiveness of measures in monetary terms, for example, looking at the physical capabilities of the measures themselves. We know there are a range of intangible or nonmonetary flood impacts (Bubeck, Otto, & Weichselgartner, 2017b), like psychological or mental health impacts (Foudi, Osés-Eraso, & Galarraga, 2017) or well-being losses (Hudson, Pham, & Bubeck, 2019c). Thieken et al (2016a) and Reiter, Wenzel, Dittmer, Lorenz, and Voss (2018) found that households can perceive psychological stress and recovery activities more seriously than financial losses.…”
Section: Knowledge Limitationsmentioning
confidence: 99%
“…Furthermore, a core epistemological limitation with very practical implications results from the research being overwhelmingly focused on understanding the effectiveness of measures in monetary terms, for example, looking at the physical capabilities of the measures themselves. We know there are a range of intangible or nonmonetary flood impacts (Bubeck, Otto, & Weichselgartner, 2017b), like psychological or mental health impacts (Foudi, Osés-Eraso, & Galarraga, 2017) or well-being losses (Hudson, Pham, & Bubeck, 2019c). Thieken et al (2016a) and Reiter, Wenzel, Dittmer, Lorenz, and Voss (2018) found that households can perceive psychological stress and recovery activities more seriously than financial losses.…”
Section: Knowledge Limitationsmentioning
confidence: 99%
“…Floods can impact societies in multiple ways, ranging from the loss of life, injuries and mental health effects to the destruction of assets (Bubeck, Otto, & Weichselgartner, 2017), which results flooding being considered as the most significant natural hazard to affect humanity (UNISDR, 2011). Asia is especially prone to flood impactsfor example, a typhoon in November 2017 resulted in around 110 deaths and a monetary loss of 650 million USD across the Philippines and Vietnam (Munich Re, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of documenting gender differences in disaster impacts has been recently highlighted (Cutter, 2017). Another shortcoming of the existing literature is its focus on industrialized countries, despite the fact that the majority of floodaffected people live in developing countries, mainly in Asia (Bubeck et al, 2017). Consequently, there is currently a lack of insights into the cross-comparability and transferability of the impacts of floods on SWB.…”
Section: Introductionmentioning
confidence: 99%
“…Flood water absorbed underground recharges the underground aquifers to supply fresh water to rivers, wells, dams, and lakes from flood water to the extent that many countries are dependent on aquifers for fresh water. Floods are an alternating source of that fresh water supply [11]. Ecosystems also depend on flood water which carries and deposits nutrients rich in sediments that support both the plant and animal life of wetlands [12].…”
Section: Associated Flood Benefitsmentioning
confidence: 99%